Effect of Adding Continous Irrigation to Arthroscopic Debridement of Septic Knee: A Retrospective Study - Thanikachalam, Ramakrishnan; Selvaraj, R. (Journal of Neonatal Surgery, 2025)
Even with current advancements in the field of orthopedics, septic/infective arthritis of knee remains an unsettling nightmare. Early mobilization and rehabilitation has now become possible with the advent of arthroscopic debridement, but still recurrence remains awful. The aim of this study is to retrospectively analyze the outcomes of patients who were treated with a novel method of continuous irrigation following arthroscopic debridement in patients who presented with infective/septic arthritis. The data of all the patients who were treated with continuous irrigation for following arthroscopic debridement, between Jan 2018 to Dec 2022 were collected and retrospectively analyzed. After a mean follow up of 25 months there was no recurrence in all the 24 patients who qualified our inclusion criteria, 3 patients had post operative stiffness among them 2 were treated with physical therapy and one who didn’t improve with physical therapy also denied surgical correction. The mean post operative KOOS score was 78.2 ± 3.8 which was significantly higher compared to their pre-operative scores. Adding continuous irrigation to arthroscopic debridement proves to be an effective, promising treatment for septic/infective arthritis rather than arthroscopic debridement alone to avoid recurrences.